DAMPAK KEBIJAKAN DIVIDEN, KEPEMILIKAN MANEJERIAL, DAN MODAL INTELEKTUAL TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING - Nuur, Harzuna Said; Fandiyanto, Randika; Ariyantiningsih, Febri (Fakultas Ekonomi dan Bisnis, 2024)
Dividend distribution policy is a company's decision regarding how to distribute profits that have been obtained, whether to distribute to investors or to reinvest in the company. A consideration that companies need to take into account when distributing dividends is how much dividend will be paid to shareholders compared to the amount that will be reinvested in the company. At its core, dividends are a cash flow given to shareholders, but retained earnings are also an effective way to fund company growth. The aim of this research is to analyze and test